2006
DOI: 10.1021/jp0611830
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene Adsorption from Solution on Single Wall Carbon Nanotubes

Abstract: Phenanthrene was adsorbed from ethanol solution to the surface of single wall carbon nanotubes, which were previously physically and chemically characterized. Different anionic surfactants were added in the solutions to enhance the phenanthrene solubility and apparently have also improved the dispersion of two respective nanotube samples used. Adsorbed amount was determined through the concentration difference measured by UV-visible spectrophotometry. Results suggest that adsorption of phenanthrene is extremel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 24 publications
1
70
1
Order By: Relevance
“…In general it is difficult or even impossible to differentiate between these states or processes, and they may be described as sorption processes (not distinguishing between ad-or absorption). CNTs have been used for the sorption of a variety of organic compounds from water such as dioxins (Long and Yang 2001), polyaromatic hydrocarbons (PAH) (Gotovac et al 2006), polybrominated diphenyl ether (PBDEs) ) chlorobenzenes and chlorophenols (Cai et al 2005;Peng et al 2003) and pesticides thiamethoxam (Zhou et al 2006). Oxidized and hydroxylated CNTs have also been used for the sorption of metals such as copper , nickel (Chen and Wang 2006), cadmium (Liang et al 2004), lead (Li et al 2002), silver , zinc (Lu and Chiu 2006), americium(III) ) and rare earth metals (Liang et al 2005).…”
Section: Interaction With Pollutantsmentioning
confidence: 99%
“…In general it is difficult or even impossible to differentiate between these states or processes, and they may be described as sorption processes (not distinguishing between ad-or absorption). CNTs have been used for the sorption of a variety of organic compounds from water such as dioxins (Long and Yang 2001), polyaromatic hydrocarbons (PAH) (Gotovac et al 2006), polybrominated diphenyl ether (PBDEs) ) chlorobenzenes and chlorophenols (Cai et al 2005;Peng et al 2003) and pesticides thiamethoxam (Zhou et al 2006). Oxidized and hydroxylated CNTs have also been used for the sorption of metals such as copper , nickel (Chen and Wang 2006), cadmium (Liang et al 2004), lead (Li et al 2002), silver , zinc (Lu and Chiu 2006), americium(III) ) and rare earth metals (Liang et al 2005).…”
Section: Interaction With Pollutantsmentioning
confidence: 99%
“…The main interactions responsible for the adsorptions of organic compounds by CNTs are: hydrophobic effect, π-electron donor−acceptor (π-EDA) bonds and hydrogen bonds [18][19][20]. Multilayer adsorption may also occur when doi: 10.7243/2050-1323-3-2 organic chemicals are adsorbed on the surface of CNTs [21]. In addition, it has been shown that CNTs display faster desorption for a wide range of nonpolar compounds [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclohexane cannot form π-π interactions and Molecules are assumed to be adsorbed such that the molecular axis is parallel to the nanotube axis (Gotovac et al, 2007a) (a) (b) hydrogen bonds with CNPs because it has no functional groups. It is widely recognized that the effect of molecular functional groups on adsorption of organic contaminants by CNTs is by π-π electrondonor-acceptor (EDA) interaction (Gotovac et al, 2006;Chen et al, 2007). The strength of EDA interaction is greatly dependent on the functional groups attached to the benzene rings of organic contaminants.…”
Section: Molecular Functional Groupsmentioning
confidence: 99%
“…Among these interactions, hydrophobic interaction has been used to interpret the sorption of hydrophobic organic contaminants (HOCs) by CNPs, because the surfaces of CNPs are hydrophobic (Gotovac et al, 2006;2007c;Yang et al, 2006). Electrostatic interaction may be the dominant interaction for the adsorption of charged organic contaminants on CNPs (MacKay and Vasudevan, 2012), such as the adsorption of fluoroquinolone antibiotics (OFL and NOR) on CNTs, as affected by pH (Wang et al, 2009;Peng et al, 2012b).…”
Section: Mechanisms Of Interaction Between Contaminants and Carbon Namentioning
confidence: 99%